2004
DOI: 10.1103/physrevb.69.134522
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional nature of superconductivity in the intercalated layered systemsLixHfNClandLi

Abstract: We report muon spin relaxation (µSR) and magnetization measurements, together with synthesis and characterization, of the Li-intercalated layered superconductors Li x HfNCl and Li x ZrNCl with/without co-intercalation of THF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 53 publications
7
36
2
Order By: Relevance
“…For Li x ZrNCl, Hiraishi et al have found that the anisotropy becomes stronger with increasing x [46], which is consistent with the specific heat measurements. Strongcoupling superconductivity was also confirmed by µSR experiments for both Li x ZrNCl and Li x (THF) y HfNCl [46,47]…”
Section: µSr and Tunneling Measurementsmentioning
confidence: 61%
See 1 more Smart Citation
“…For Li x ZrNCl, Hiraishi et al have found that the anisotropy becomes stronger with increasing x [46], which is consistent with the specific heat measurements. Strongcoupling superconductivity was also confirmed by µSR experiments for both Li x ZrNCl and Li x (THF) y HfNCl [46,47]…”
Section: µSr and Tunneling Measurementsmentioning
confidence: 61%
“…s /m * , rather than the 3D counter part, n 3D s /m * , is the dominant factor for determining the high T c in the nitride superconductors, and suggested similarity to overdoped cuprates [47], implying 2D nature and unconventional superconductivity in the nitride superconductors.…”
Section: Dmentioning
confidence: 97%
“…SR measurements (T. Ito et al [639]) on -Lix(Hf,Zr)NCl, both with and without co-intercalated THF/PC, were interpreted as strongly favoring 2D superconductivity with only weak interlayer coupling. (This is of course in contrast to the data for -TiNCl in Fig.…”
Section: Superconducting Properties That Impinge On Possible Ucs -Formmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) 11 and muon spin relaxation measurements 12,13 have suggested the quasi two-dimensional superconductors. Regardless of the relatively high T c , the T -linear specific heat has been found to be very small (∼ 1mJ/mol 2 ).…”
Section: Introductionmentioning
confidence: 99%